Graphene fiber composite film, preparation method thereof and electric heating material

By pre-depositing solid pyrolytic carbon on the inner wall of the reaction device and adjusting the orientation of the fiber material, the problem of uneven thickness of graphene fiber composite film was solved, and uniform heating and rapid response of the electric heating material were achieved.

CN121152069APending Publication Date: 2025-12-16胡平安
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511360018.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

In the prior art, when preparing graphene fiber composite films by chemical vapor deposition, uneven flow of gaseous carbon source leads to uneven film thickness, which affects the heating uniformity of the electric heating material.

Method used

Solid pyrolytic carbon is pre-deposited on the inner wall of the reaction device, the orientation of the inorganic fiber material is adjusted, and different airflow directions are formed through two chemical vapor deposition processes to ensure uniform carbon source distribution and promote uniform graphene growth.

Benefits of technology

A graphene fiber composite film with uniform thickness was prepared, which improved the uniformity of heating and the low-temperature response speed when applied to electric heating materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121152069A_ABST
    Figure CN121152069A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of advanced functional materials, and provides a graphene fiber composite film, a preparation method thereof and an electric heating material. Solid-state pyrolytic carbon is pre-deposited on the inner wall of a reaction device, in the subsequent chemical vapor deposition process, the solid-state pyrolytic carbon is directly deposited on the surface of the inorganic fiber under hydrogen etching or becomes gaseous methane or CH3 / CH2 / CH free radicals again, vapor chemical deposition is conducted on the surface of the inorganic fiber material, different airflow directions are formed, and the surface of the inorganic fiber material is subjected to chemical vapor deposition. The problem of non-uniform carbon source concentration caused by deposition of the carbon source along a single airflow direction is solved, and the thickness uniformity of the graphene fiber composite film is improved; after the first chemical vapor deposition, the two ends of the inorganic fiber material along the introduction direction of the gaseous carbon source are turned by 180 degrees, and then the second chemical vapor deposition is performed, so that the problem of non-uniform growth of graphene caused by non-uniform carbon source concentration due to the deposition of the carbon source along the airflow direction is solved, and the uniform growth of graphene is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of advanced functional materials technology, and in particular to a graphene fiber composite membrane and its preparation method, as well as an electric heating material. Background Technology

[0002] Graphene fiber composite films are multifunctional materials synthesized from graphene and a fiber matrix through a specific process. They possess properties such as high strength, high conductivity, high thermal stability, and high transparency, making them promising for applications in electronics, optoelectronics, and energy. Current technology typically employs chemical vapor deposition (CVD) to place the fiber matrix in a reactor and then introduce a specific flow rate of gaseous carbon source. This causes the gaseous carbon source to decompose into active carbon atoms, which are then deposited on the surface of the fiber matrix to obtain the graphene fiber composite film. This method can produce high-quality graphene fiber composite films with high controllability and is suitable for large-area fabrication. However, during CVD, the gaseous carbon source flow distribution is uneven, the free path is short, and the carbon source accumulates continuously along the gas flow direction, resulting in uneven thickness of the graphene fiber composite film. This uneven heating can also occur when the resulting graphene fiber composite film is used in electric heating materials. Summary of the Invention

[0003] The purpose of this invention is to provide a graphene fiber composite film, its preparation method, and an electric heating material. The graphene fiber composite film prepared by the method provided by this invention has uniform thickness and sheet resistance, and can achieve uniform heating when applied to electric heating materials.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0005] This invention provides a method for preparing a graphene fiber composite membrane, comprising:

[0006] Solid pyrolytic carbon is pre-deposited on the inner wall of the reaction device;

[0007] Inorganic fiber material is placed in the reaction device, and gaseous carbon source and hydrogen are introduced. First chemical vapor deposition and second chemical vapor deposition are performed in sequence to obtain graphene fiber composite film.

[0008] After the first chemical vapor deposition, the inorganic fiber material is rotated 180° at both ends along the direction in which the gaseous carbon source is introduced;

[0009] The inorganic fiber material can be in the form of inorganic fiber cloth, inorganic fiber tape, or inorganic fiber sleeve.

[0010] Preferably, the gas pressure of the first chemical vapor deposition and the second chemical vapor deposition is independently 10. -1 ~10 5Pa, the temperatures of the first chemical vapor deposition and the second chemical vapor deposition are independently 600–1200 °C, and the times of the first chemical vapor deposition and the second chemical vapor deposition are independently 10–240 min.

[0011] Preferably, the thickness of the solid pyrolytic carbon is 0.1–5 μm.

[0012] Preferably, the flow rate of the gaseous carbon source is 1-200 sccm, and the flow rate of the hydrogen is 1-500 sccm.

[0013] Preferably, the gaseous carbon source includes one or more of methane, ethylene, and acetylene.

[0014] Preferably, the graphene fiber composite membrane contains 1 to 30 layers of graphene.

[0015] Preferably, the inorganic fiber material is subjected to annealing, plasma etching, and coupling agent grafting in sequence before use.

[0016] Preferably, the inorganic fiber material includes glass fiber, quartz fiber, or alumina fiber.

[0017] The present invention also provides a graphene fiber composite membrane prepared by the above-described preparation method, comprising an inorganic fiber material and a graphene membrane attached to the surface of the inorganic fiber material.

[0018] The present invention also provides an electric heating material, comprising a graphene fiber composite film and copper foil electrodes disposed on both sides of the graphene fiber composite film, wherein the graphene fiber composite film is the graphene fiber composite film prepared by the preparation method described in the above technical solution; and a graphene film is attached to the surface of the copper foil electrodes.

[0019] The method for preparing a graphene fiber composite membrane provided by the present invention includes: pre-depositing solid pyrolytic carbon on the inner wall of a reaction device; placing an inorganic fiber material in the reaction device, introducing a gaseous carbon source and hydrogen, and sequentially performing a first chemical vapor deposition and a second chemical vapor deposition to obtain a graphene fiber composite membrane; after the first chemical vapor deposition, rotating the inorganic fiber material by 180° at both ends along the direction in which the gaseous carbon source is introduced; the inorganic fiber material includes inorganic fiber cloth, inorganic fiber tape, or inorganic fiber sleeve. This invention pre-deposits solid pyrolytic carbon on the inner wall of a reaction device. During subsequent chemical vapor deposition (CVD), the solid pyrolytic carbon distributed on the inner wall of the reaction device is directly deposited onto the surface of inorganic fibers under hydrogen etching, or it reverts to gaseous methane or CH3 / CH2 / CH radicals for CVD deposition on the inorganic fiber material surface. This creates different carbon source gas flow directions, reducing the problem of uneven carbon source concentration caused by deposition along a single gas flow direction, and improving the uniformity of the graphene fiber composite film thickness. Furthermore, by rotating the inorganic fiber material 180° at both ends along the direction of gaseous carbon source introduction after the first CVD, followed by a second CVD deposition, the problem of uneven carbon source concentration caused by deposition along the gas flow direction, thus preventing uneven graphene growth, is further eliminated, promoting uniform graphene growth. The results of the embodiments show that the graphene fiber composite film prepared by this invention has a uniform thickness, and the electrically heated material exhibits uniform heating. Attached Figure Description

[0020] Figure 1 This is a schematic diagram showing the graphene fiber composite membrane prepared in Example 1 of the present invention, in which the fiber cloth is rotated 180° at both ends along the direction of gaseous carbon source introduction after the first chemical vapor deposition.

[0021] Figure 2 This is a schematic diagram of the structure of the electric heating material prepared in Application Example 1 of the present invention;

[0022] Figure 3 EDS image of the graphene fiber composite membrane prepared in Example 1 of this invention;

[0023] Figure 4 The Raman spectrum of the graphene fiber composite membrane prepared in Example 1 of this invention;

[0024] Figure 5 The image shows the actual graphene fiber composite membrane prepared in Example 1 of this invention, as well as its twisted, bent, folded, and spread-out images.

[0025] Figure 6 The sheet resistance distribution diagrams of the graphene fiber composite films obtained after the first chemical vapor deposition and the second chemical vapor deposition in Example 1 of the present invention are shown.

[0026] Figure 7The Raman spectrum of the graphene copper foil electrode in the electric heating material prepared in Application Example 1 of this invention;

[0027] Figure 8 An optical micrograph of the graphene copper foil electrode in the electric heating material prepared in Application Example 1 of this invention after oxidation at 200°C for 8 hours;

[0028] Figure 9 Infrared thermal imaging of the electric heating material prepared in Application Example 1 of this invention;

[0029] Figure 10 The electric heating temperature response diagram of the electric heating material prepared in Application Example 1 of the present invention at a voltage of 20V is shown. Detailed Implementation

[0030] This invention provides a method for preparing a graphene fiber composite membrane, comprising:

[0031] Solid pyrolytic carbon is pre-deposited on the inner wall of the reaction device;

[0032] Inorganic fiber material is placed in the reaction device, and gaseous carbon source and hydrogen are introduced. First chemical vapor deposition and second chemical vapor deposition are performed in sequence to obtain graphene fiber composite film.

[0033] The present invention pre-deposits solid pyrolytic carbon on the inner wall of the reaction device.

[0034] In this invention, solid pyrolytic carbon is pre-deposited on the inner wall of the reaction device. During the subsequent chemical vapor deposition process, the solid pyrolytic carbon distributed on the inner wall of the reaction device is transformed back into a gaseous carbon source, forming different airflow directions. This reduces the problem of uneven carbon source concentration caused by carbon source deposition along the airflow direction and improves the uniformity of the graphene fiber composite film thickness.

[0035] In this invention, the thickness of the solid pyrolytic carbon is preferably 1–30 nm. In embodiments of this invention, the thickness of the solid pyrolytic carbon can specifically be 1 nm, 10 nm, 20 nm, or 30 nm. This invention, by limiting the thickness of the solid pyrolytic carbon, ensures that the solid pyrolytic carbon distributed on the inner wall of the reaction device is re-converted into a gaseous carbon source during the subsequent chemical vapor deposition process, forming different airflow directions. This more effectively reduces the problem of uneven carbon source concentration caused by carbon source deposition along the airflow direction, thereby improving the uniformity of the graphene fiber composite film thickness.

[0036] This invention does not impose any particular limitation on the reaction apparatus; any reaction apparatus well-known in the art for chemical vapor deposition can be used. In this invention, the reaction apparatus is preferably a tube furnace.

[0037] In this invention, the method for pre-depositing solid pyrolytic carbon on the inner wall of the reaction device preferably includes: introducing a carbon source into the reaction device and then performing pyrolysis to obtain pre-deposited solid pyrolytic carbon.

[0038] In this invention, the carbon source includes a gaseous carbon source or a liquid carbon source. Preferably, the gaseous carbon source includes one or more of methane, ethylene, and acetylene. Preferably, the liquid carbon source includes one or more of methanol, toluene, ethanol, acetone, n-hexane, and cyclohexane. This invention ensures more complete carbon-hydrogen bond breaking during pyrolysis to obtain carbon atoms and hydrogen gas by limiting the type of carbon source. The flow rate of the carbon source is preferably 1–200 sccm. In embodiments of this invention, the flow rate can specifically be 1 sccm, 50 sccm, 100 sccm, 150 sccm, or 200 sccm. This invention further ensures more complete carbon-hydrogen bond breaking to obtain carbon atoms and hydrogen gas by limiting the flow rate of the carbon source, thereby obtaining solid pyrolytic carbon.

[0039] In this invention, the pyrolysis temperature is preferably 300–800°C. In embodiments of this invention, the pyrolysis temperature may specifically be 300°C, 400°C, 500°C, 600°C, 700°C, or 800°C. In this invention, the pyrolysis time is preferably 1–4 hours. In embodiments of this invention, the pyrolysis time may specifically be 1 hour, 2 hours, 3 hours, or 4 hours. This invention ensures that the carbon source is more fully pyrolyzed to form carbon atoms, which are then deposited on the inner wall of the reaction apparatus to form a solid pyrolytic carbon of a certain thickness.

[0040] In this invention, argon gas is preferably introduced during the pyrolysis process. The preferred flow rate of the argon gas is 1–200 sccm. In embodiments of this invention, the flow rate of the argon gas can specifically be 1 sccm, 50 sccm, 100 sccm, 150 sccm, or 200 sccm.

[0041] After pyrolysis is completed, the present invention preferably cools the pyrolysis product to obtain pre-deposited solid pyrolytic carbon.

[0042] After pre-depositing solid pyrolytic carbon on the inner wall of the reaction device, the present invention places inorganic fiber material in the reaction device, introduces gaseous carbon source and hydrogen, and performs first chemical vapor deposition and second chemical vapor deposition in sequence to obtain graphene fiber composite film.

[0043] In this invention, the inorganic fiber material preferably includes glass fiber, quartz fiber, or alumina fiber. The inorganic fiber material preferably exists in the form of inorganic fiber cloth, inorganic fiber felt, inorganic fiber tape, or inorganic fiber sleeve. This invention ensures the preparation of a flexible graphene fiber composite membrane by limiting the type and form of the inorganic fiber material.

[0044] In one specific embodiment, when the inorganic fiber material is in the form of inorganic fiber cloth or inorganic fiber felt, the inorganic fiber cloth or inorganic fiber felt can be rolled into a cylindrical shape. This invention achieves a larger area graphene fiber composite membrane by rolling the inorganic fiber cloth or inorganic fiber felt into a cylindrical shape.

[0045] The present invention does not impose any special limitations on the size of the inorganic fiber material, as long as it meets the actual needs.

[0046] In this invention, the inorganic fiber material is preferably subjected to annealing, plasma etching, coupling agent grafting, and drying in sequence before use.

[0047] In this invention, the annealing temperature is preferably 300–900°C. In embodiments of this invention, the annealing temperature may specifically be 300°C, 500°C, 600°C, 700°C, or 900°C. In this invention, the annealing time is preferably 0.5–3 hours. In embodiments of this invention, the annealing time may specifically be 0.5 hours, 1 hour, 2 hours, or 3 hours. In this invention, the annealing atmosphere is preferably carried out in an argon-oxygen mixed atmosphere. In this invention, the volume of oxygen in the argon-oxygen mixed atmosphere is preferably 0.5%–50% of the argon-oxygen mixture. In embodiments of this invention, the volume of oxygen in the argon-oxygen mixed atmosphere may specifically be 0.5%, 5%, 10%, 20%, 30%, 40%, or 50% of the argon-oxygen mixture. This invention ensures more thorough removal of organic adhesives and resins from the surface of inorganic fibers by limiting the annealing parameters.

[0048] In this invention, the radio frequency power of the plasma etching is preferably 100–500 W. In embodiments of this invention, the radio frequency power of the plasma etching can be 100 W, 200 W, 300 W, 400 W, or 500 W. In this invention, the plasma etching time is preferably 15–90 min. In embodiments of this invention, the plasma etching time can be 15 min, 30 min, 60 min, or 90 min. In this invention, the gas used for plasma etching is preferably argon and oxygen. In this invention, the flow rates of the argon and oxygen are independently preferably 10–100 sccm. In embodiments of this invention, the flow rates of the argon and oxygen can be independently specifically 10 sccm, 20 sccm, 50 sccm, 70 sccm, or 100 sccm. In this invention, by limiting the parameters of plasma etching, the present invention ensures that nucleation sites can be formed more fully on the surface of the inorganic fiber.

[0049] In this invention, the coupling agent is preferably a silane coupling agent. This invention employs a coupling agent to graft onto the surface of inorganic fibers, utilizing the -OH groups on the silane coupling agent as highly active sites, which facilitates the stable anchoring of the initial carbon atoms or small carbon clusters. In this invention, the method of grafting the coupling agent preferably includes: immersing the plasma-etched inorganic fiber material in the coupling agent. In this invention, the immersion time is preferably 30–90 minutes. In embodiments of this invention, the immersion time can specifically be 30 minutes, 60 minutes, or 90 minutes. This invention ensures more complete grafting of the silane coupling agent onto the surface of the inorganic fibers by limiting the immersion temperature and time, thereby resulting in a stronger connection with graphene.

[0050] In this invention, the drying temperature is preferably 70–120°C. In embodiments of this invention, the drying temperature may specifically be 70°C, 90°C, or 120°C. In this invention, the drying time is preferably 60–120 min. In embodiments of this invention, the drying time may specifically be 60 min, 80 min, 100 min, or 120 min.

[0051] In this invention, the gaseous carbon source preferably includes one or more of methane, ethylene, and acetylene. This invention ensures that the gaseous carbon source decomposes into carbon atoms during chemical vapor deposition and deposits on the surface of inorganic fibers to obtain a graphene film.

[0052] In this invention, the flow rate of the gaseous carbon source is preferably 1–200 sccm. In embodiments of this invention, the flow rate of the gaseous carbon source can specifically be 1 sccm, 50 sccm, 100 sccm, 150 sccm, or 200 sccm. This invention limits the flow rate of the gaseous carbon source to ensure that it is further and fully decomposed into carbon atoms during the chemical vapor deposition process and deposited on the surface of the inorganic fibers to obtain a graphene film.

[0053] In this invention, hydrogen participates in the catalytic cracking reaction of gaseous carbon sources, reducing the cracking activation energy and increasing the carbon atom yield. Simultaneously, it acts as an etchant for solid pyrolytic carbon, allowing solid pyrolytic carbon atoms to be directly deposited on the surface of inorganic fiber materials or to revert to gaseous methane or CH3 / CH2 / CH radicals for vapor-phase chemical deposition on the inorganic fiber material surface. In this invention, the hydrogen flow rate is preferably 1–500 sccm. In embodiments of this invention, the hydrogen flow rate can specifically be 1 sccm, 50 sccm, 100 sccm, 300 sccm, or 500 sccm. This invention further promotes the catalytic cracking of gaseous carbon sources and further promotes the recombination of solid pyrolytic carbon into gaseous carbon sources by limiting the hydrogen flow rate.

[0054] In this invention, the carrier gas for the gaseous carbon source is preferably argon or nitrogen. The flow rate of the carrier gas is preferably 1–500 sccm. In embodiments of this invention, the flow rate of the carrier gas can specifically be 1 sccm, 50 sccm, 100 sccm, 300 sccm, or 500 sccm.

[0055] In this invention, the gas pressure of the first chemical vapor deposition is preferably 10. -1 ~10 5 Pa. In a specific embodiment of the present invention, the gas pressure of the first chemical vapor deposition may specifically be 10 Pa. -1 Pa, 10Pa, 100Pa, 1000Pa, 10 4 Pa, 10 5Pa. This invention improves the deposition rate by limiting the gas pressure of the first chemical vapor deposition (CVD) to increase the diffusion rate and collision frequency of the gaseous carbon source in the gas phase. In this invention, the temperature of the first CVD is preferably 600–1200°C. In specific embodiments of this invention, the temperature of the first CVD can be 600°C, 700°C, 800°C, 900°C, 1050°C, or 1200°C. In this invention, the heating rate of the first CVD is preferably 10°C / min. In this invention, the time of the first CVD is preferably 10–240 min. In specific embodiments of this invention, the time of the first CVD can be 10 min, 30 min, 50 min, 100 min, 150 min, 180 min, 210 min, or 240 min. This invention, by limiting the temperature and time of the first CVD, ensures that the gaseous carbon source can be deposited more fully on the surface of the inorganic fiber to obtain a certain number of graphene layers.

[0056] After the first chemical vapor deposition, the present invention preferably cools the inorganic fiber material after the first chemical vapor deposition, and then rotates the cooled inorganic fiber material by 180° at both ends along the direction of the gaseous carbon source introduction before performing a second chemical vapor deposition to obtain a graphene fiber composite film.

[0057] In this invention, after the first chemical vapor deposition, the inorganic fiber material is rotated 180° at both ends along the direction of the gaseous carbon source inlet before the second chemical vapor deposition is performed. This can further eliminate the problem of uneven carbon source concentration caused by the carbon source depositing along the gas flow direction, which in turn causes uneven graphene growth, and promote uniform graphene growth.

[0058] In this invention, the gas pressure, temperature, heating rate, time, carrier gas and catalyst parameters of the second chemical vapor deposition are the same as those of the first chemical vapor deposition, and will not be repeated here.

[0059] After the second chemical vapor deposition is completed, the product of the second chemical vapor deposition is cooled to obtain a graphene fiber composite film.

[0060] In this invention, the number of graphene layers in the graphene fiber composite film is preferably 1 to 30. This invention ensures a fast low-temperature response speed for the resulting electric heating material by limiting the number of graphene layers in the graphene fiber composite film.

[0061] This invention pre-deposits solid pyrolytic carbon on the inner wall of the reaction device. During the subsequent chemical vapor deposition process, the solid pyrolytic carbon distributed on the inner wall of the reaction device is transformed back into a gaseous carbon source, forming different airflow directions. This reduces the problem of uneven carbon source concentration caused by carbon source deposition along the airflow direction, and improves the uniformity of graphene fiber composite film thickness. By limiting the inorganic fiber material to be rotated 180° at both ends along the direction of gaseous carbon source introduction after the first chemical vapor deposition, and then performing the second chemical vapor deposition, the problem of uneven carbon source concentration caused by carbon source deposition along the airflow direction, which in turn causes uneven graphene growth, is further eliminated, promoting uniform graphene growth.

[0062] The present invention also provides an electric heating material, comprising a graphene fiber composite film and copper foil electrodes disposed on both sides of the graphene fiber composite film, wherein the graphene fiber composite film is the graphene fiber composite film prepared by the preparation method described in the above technical solution; and a graphene film is attached to the surface of the copper foil electrodes.

[0063] In this invention, the copper foil electrodes are preferably disposed on both sides of the wide side of the graphene fiber composite film. In this invention, each copper foil electrode is preferably independently formed by welding several copper foils with a length gradient. This invention overcomes the edge effect of the electrodes by limiting the copper foils to different length gradients, avoiding current concentration around the electrodes and improving the heating uniformity of the electric heating material. In this invention, the copper foil is preferably rolled copper foil. In this invention, the length of the copper foil electrodes preferably decreases from the edge of the wide side of the graphene fiber composite film towards the center. In this invention, the edge length of the copper foil electrodes is preferably the same as the wide side of the graphene fiber composite film. In this invention, the length gradient value of the copper foil electrodes is preferably 1 cm. In this invention, the width of each copper foil electrode is preferably 0.1 to 1 cm. In embodiments of this invention, the width of each copper foil electrode can specifically be 0.1 cm, 0.5 cm, 0.8 cm, or 1 cm. In this invention, the welding material is preferably silver paste. This invention does not have a special limitation on the source of the silver paste; commercially available silver paste can be used. In this invention, the silver content in the commercially available silver paste is preferably ≥60wt%.

[0064] In this invention, a graphene film is preferably attached to the surface of the copper foil electrode. In this invention, the graphene film deposited on the copper foil surface forms a graphene protective layer to improve the oxidation resistance of the copper foil electrode. In this invention, the graphene film is preferably a single layer. This invention further protects the copper foil and improves the oxidation resistance of the copper foil electrode by limiting the number of graphene film layers. This invention does not have a particular limitation on the preparation method of the graphene film; graphene can be deposited on the surface of the copper foil electrode using methods well-known in the art. In this invention, the graphene deposition method is preferably chemical vapor deposition.

[0065] The electric heating material provided by this invention has good heating uniformity and fast low-temperature response speed.

[0066] To further illustrate the present invention, the following detailed description of the invention's solutions, in conjunction with the accompanying drawings and embodiments, is provided, but should not be construed as limiting the scope of protection of the present invention.

[0067] Example 1

[0068] A method for preparing a graphene fiber composite membrane:

[0069] 100 sccm of acetylene and 200 sccm of argon were introduced into a tube furnace and pyrolyzed at 700℃ for 2 hours to obtain pre-deposited solid pyrolytic carbon with a thickness of 10 nm.

[0070] A 20×24cm alumina fiber cloth (72% alumina, 28% silicon dioxide) was placed in the tubular furnace that was rolled into a cylinder. 100 sccm of argon, 100 sccm of hydrogen and 50 sccm of methane were introduced, and first plasma-enhanced chemical vapor deposition and second plasma-enhanced chemical vapor deposition were performed in sequence to obtain a graphene fiber composite film.

[0071] The alumina fiber cloth is subjected to annealing, plasma etching, coupling agent grafting and drying in sequence before use;

[0072] The annealing temperature is 600℃, and the annealing time is 2 hours. The annealing is carried out in an argon-oxygen mixed atmosphere, where the volume of oxygen is 10% of the argon-oxygen mixture. The radio frequency power of the plasma etching is 400W (13.56MHz), and the plasma etching time is 30 minutes. The plasma etching gas consists of 90 sccm of argon and 10 sccm of oxygen. Finally, the plasma-etched alumina fiber cloth is immersed in a 5wt% KH-550 coupling agent aqueous solution for 60 minutes. The drying temperature is 70℃, and the drying time is 60 minutes.

[0073] The temperature of the first chemical vapor deposition was 1050℃, the heating rate was 10℃ / min, and the deposition time was 30min; then, the furnace was cooled, and the alumina fiber cloth was rotated 180° at both ends along the direction of methane introduction, as follows. Figure 1 As shown, a second chemical vapor deposition was performed, followed by furnace cooling to obtain a 24cm×20cm graphene fiber composite film with 20-25 graphene layers.

[0074] Application Example 1

[0075] An electric heating material, such as Figure 2As shown, the graphene fiber composite film, prepared by the example, consists of a 24cm × 20cm graphene fiber composite film and rolled copper foil electrodes disposed on both sides of the graphene fiber composite film. The rolled copper foil electrodes are disposed on both sides of the wide edge of the graphene fiber composite film. Each side of the rolled copper foil electrode is independently formed by welding three copper foils with a length gradient. The welding material is silver paste with a silver content ≥60wt%. The length of the copper foil electrode decreases from the edge of the wide edge of the graphene fiber composite film towards the middle. The edge length of the copper foil electrode is the same as the wide edge of the graphene fiber composite film. The length gradient value of the copper foil electrode is 1cm. The width of each copper foil electrode is 1mm. A single layer of graphene film is attached to the surface of the copper foil electrode.

[0076] The method for attaching graphene to the surface of the copper foil electrode is as follows: by chemical vapor deposition, in a hydrogen-argon mixture (hydrogen flow rate 20 sccm, argon flow rate 100 sccm), with methane as the carbon source (flow rate 5 sccm), at 1045℃ for 20 min.

[0077] The elemental composition of the graphene fiber composite film prepared in Example 1 was characterized using scanning electron microscopy. Figure 3 As shown in the figure. From the figure, we can see that: Figure 3 The four elemental spectra on the right contain aluminum, silicon, oxygen, and carbon, with carbon concentrated on the fiber surface, indicating that graphene grows on the fiber surface.

[0078] The structure of the graphene fiber composite membrane prepared in Example 1 was characterized using Raman spectroscopy. Figure 4 As shown in the figure, the peak intensity I in the figure can be seen as follows: 2D / I G <1 indicates that the graphene in the graphene fiber composite film is multilayered.

[0079] The graphene fiber composite membrane prepared in the examples was twisted, bent, folded, and spread as follows: Figure 5 As shown in the figure, the graphene fiber composite membrane prepared by this invention has good flexibility.

[0080] The sheet resistance of the graphene fiber composite films obtained in Example 1 after the first chemical vapor deposition and the second chemical vapor deposition was measured using a four-probe sheet resistance meter. The sheet resistance distribution diagrams are shown below. Figure 6As shown in the figures, Figures a and c represent the sheet resistance of the graphene fiber composite film after 30 min and 35 min of the first chemical vapor deposition (CVD), respectively; Figures b and d represent the sheet resistance of the graphene fiber composite film after 30 min and 35 min of the second CVD, respectively. It can be seen from the figures that the sheet resistance distribution of the graphene fiber composite film after 30 min and 35 min of the second CVD is more uniform than that after the first CVD. Furthermore, the sheet resistance distribution range of the graphene fiber composite film after 35 min of the second CVD is smaller than that of the graphene fiber composite film after 30 min of the second CVD, which is beneficial for improving the response speed of the electrothermal material.

[0081] The graphene in the graphene-copper foil electrode of the electric heating material prepared in Example 1 was characterized using Raman spectroscopy, as shown in Example 1. Figure 7 As shown in the figure, the peak intensity I 2D / I G The value is greater than 1, and there is no D peak, indicating that a monolayer of graphene with good crystallinity has been grown on the graphene copper foil electrode.

[0082] The morphology of the graphene-coated copper foil electrode and the uncoated copper foil electrode in the electrically heated material prepared according to Example 1 were characterized using optical microscopy after oxidation at 200℃ for 8 hours. The results are as follows: Figure 8 The left and right figures are shown. As can be seen from the figures, the graphene copper foil electrode in the electric heating material of the present invention was not oxidized after oxidation at 200°C for 8 minutes; while the copper foil electrode without graphene coating changed color after oxidation at 200°C for 8 hours. It can be seen that the graphene copper foil electrode in the electric heating material of the present invention has good oxidation resistance.

[0083] The electrically heated material prepared using an infrared thermal imager, corresponding to Example 1, was subjected to infrared thermal imaging at room temperature and -30°C, respectively, as shown below. Figure 9 The left and right figures are shown in the diagram. As can be seen from the figures, the electric heating material prepared by this invention generates heat evenly.

[0084] The electric heating temperature response of the electric heating material prepared in Example 1 at a voltage of 20V, with initial temperatures of -150℃, -110℃, -40℃, and 25℃, is as follows: Figure 10 As shown in the figure, the steady-state temperatures of the electric heating material prepared in this invention after 10 seconds are 32℃, 71℃, 105℃, and 161℃, respectively, when the initial temperatures are -150℃, -110℃, -40℃, and 25℃. This indicates that the electric heating material of this invention can rapidly heat up and remain stable.

[0085] In summary, the graphene fiber composite film prepared by the method provided by this invention has uniform thickness and sheet resistance. When applied to electric heating materials, it can achieve uniform heating and has a fast response speed in the range of -150 to 25°C.

[0086] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a graphene fiber composite membrane, comprising: Solid pyrolytic carbon is pre-deposited on the inner wall of the reaction device; Inorganic fiber material is placed in the reaction device, and gaseous carbon source and hydrogen are introduced. First chemical vapor deposition and second chemical vapor deposition are performed in sequence to obtain graphene fiber composite film. After the first chemical vapor deposition, the inorganic fiber material is rotated 180° at both ends along the direction in which the gaseous carbon source is introduced; The inorganic fiber material can be in the form of inorganic fiber cloth, inorganic fiber tape, or inorganic fiber sleeve.

2. The preparation method according to claim 1, characterized in that, The gas pressures of the first and second chemical vapor depositions are independently 10. -1 ~10 5 Pa, the temperatures of the first chemical vapor deposition and the second chemical vapor deposition are independently 600–1200 °C, and the times of the first chemical vapor deposition and the second chemical vapor deposition are independently 10–240 min.

3. The preparation method according to claim 1, characterized in that, The thickness of the solid pyrolytic carbon is 0.1–5 μm.

4. The preparation method according to claim 1, characterized in that, The flow rate of the gaseous carbon source is 1–200 sccm, and the flow rate of the hydrogen is 1–500 sccm.

5. The preparation method according to claim 1 or 4, characterized in that, The gaseous carbon source includes one or more of methane, ethylene, and acetylene.

6. The preparation method according to claim 1, characterized in that, The graphene fiber composite membrane contains 1 to 30 layers of graphene.

7. The preparation method according to claim 1, characterized in that, The inorganic fiber material is subjected to annealing, plasma etching, and coupling agent grafting in sequence before use.

8. The preparation method according to claim 1 or 7, characterized in that, The inorganic fiber material includes glass fiber, quartz fiber or alumina fiber.

9. The graphene fiber composite membrane prepared by the preparation method according to any one of claims 1 to 8 comprises an inorganic fiber material and a graphene membrane attached to the surface of the inorganic fiber material.

10. An electric heating material, comprising a graphene fiber composite film and copper foil electrodes disposed on both sides of the graphene fiber composite film, characterized in that, The graphene fiber composite film is the graphene fiber composite film according to claim 9; the copper foil electrode surface is attached with a graphene film.